Navigating the New Norm: Review of Health Risks Associated with Widespread Disinfectant and Hand Sanitizer Use - Amira Raudhah Abdullah; Liyana Azmi; Muhamad Afiq Aziz; Nur Waliyuddin Hanis Zainal Abidin; Muhammad Idham Jasmiad (Medip Academy, 2026)
Tier 2- Indexed by ERA